Influence of nanobranched growth on photoelectrochemical performance of TiO2 nanotree arrays films. (May 2019) - Ning, Xiangmei; Huang, Jinliang; Li, Senlin; Li, Lihua; Gu, Yongjun; Li, Xinli; Kim, Bok H.
Abstract: TiO2 nanotree arrays films were obtained on fluorine doped tin oxide (FTO) substrates through a facile two-step hydrothermal method. The synthesized nanostructures were investigated by means of X-ray diffractometer, field-emission scanning electron microscopy and high-resolution transmission electron microscopy. The effect of TiO2 nanotree morphology on optical and photoelectrochemical performance was systematically studied using UV–Vis absorption spectra, electrochemical impedance spectroscopy (EIS), Mott-Schottky, linear voltammetry and transient photocurrent measurements. The results revealed that a TiO2 nanotree arrays film sample synthesized at 120 ℃ for nanobranched growth time 0.5 h showed a higher light trapping effect than TiO2 nanorod arrays film, and achieved relatively lower charge transport resistance and higher photocurrent density compared with the other TiO2 nanotree arrays samples. These behaviors can be mainly attributed to the formation of appropriate nanobranches manipulated the TiO2 nanotree arrays by varying the hydrothermal reaction time to improve photoexcited electrons rate under the premise of high electronic transmission performance.